Development of a Community-Based Disaster Preparedness Module: Enhancing Resilience and Response Capabilities - Suparji Suparji; Heru Santoso Wahito Nugroho; Sunarto Sunarto; Sulikah Sulikah; Astuti Setiyani; Alfi Rusdianti (Knowledge Dynamics, 2025)
Background: Disaster preparedness is one of the important aspects in reducing the negative impacts of disasters, especially in areas prone to natural disasters. This study aims to develop a community-based disaster preparedness module that can improve community resilience and response capabilities to disaster threats. This module is designed to provide practical guidance in preparedness efforts, as well as build the capacity of local communities. Methods: This study uses a research and development design with quantitative and qualitative approaches. The population in this study was the community in disaster-prone areas in Genilangit Village, Poncol District, Magetan Regency. The sample consisted of 120 respondents selected using purposive sampling techniques, with the criteria of the community who had been involved in disaster mitigation activities. The main variable in this study was community preparedness before and after the implementation of the module. The data collection instrument used a questionnaire to measure preparedness and in-depth interviews to gain qualitative insights into the implementation of the module. Quantitative data were analyzed using paired descriptive statistics to see the difference in preparedness before and after the module intervention. While qualitative data were analyzed using thematic analysis techniques. Results: The results of this study indicate that the implementation of the module significantly increased the level of community preparedness in terms of knowledge, attitudes, and skills related to disaster mitigation. Conclusion: These findings indicate that this module can be an effective tool in increasing community resilience in disaster-prone areas.